Hermann Burchardt at Siwa: unpublished pictures - Struffolino, Stefano (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
While traveling through Siwa oasis, Herman Burchardt wrote down his experiences. His report contains descriptions about the social context of the oasis or its natural environment and a note that the report is associated with “ zahlreiche wohlgelungene photographische Aufnahmen ”, not yet published. These pictures are important concerning the history of archaeological research in Siwa and wtll be first published here.